2017
DOI: 10.1155/2017/1513038
|View full text |Cite
|
Sign up to set email alerts
|

Channel Measurements and Modeling at 6 GHz in the Tunnel Environments for 5G Wireless Systems

Abstract: Propagation measurements of wireless channels performed in the tunnel environments at 6 GHz are presented in this paper. Propagation characteristics are simulated and analyzed based on the method of shooting and bouncing ray tracing/image (SBR/IM). A good agreement is achieved between the measured results and simulated results, so the correctness of SBR/IM method has been validated. The measured results and simulated results are analyzed in terms of path loss models, received power, root mean square (RMS) dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…e channel characteristics at 6 GHz in the tunnel are studied based on measurement and simulation data in [11]. It was found that the normal distribution could better fit the received power.…”
Section: Introductionmentioning
confidence: 99%
“…e channel characteristics at 6 GHz in the tunnel are studied based on measurement and simulation data in [11]. It was found that the normal distribution could better fit the received power.…”
Section: Introductionmentioning
confidence: 99%
“…Path Loss Model. PL models are commonly used to illustrate the channel effects caused by the surrounding environment, which estimate the attenuation over distance of propagating signals and are crucial for predicting the coverage probability of wireless communication systems [46,47]. In our measurement, the link budget to calculate the path loss in dB is [48] PL…”
Section: Measurement Results and Simulation Resultsmentioning
confidence: 99%
“…Consequently, modal expansion, numerical approach, and RT-based techniques of wave propagation in tunnels have significant challenges. Conversely, a large-scale path loss model was employed for model wave propagation in the tunnel [25], and the results indicate that large-scale path loss models could be effective at modelling radio wave propagation inside tunnels. Moreover, large-scale path loss models have been used to model indoor corridors [26,27] and stairwells [28].…”
Section: Introductionmentioning
confidence: 99%